Assessment of hospitalization rates for immune-related adverse events with immune checkpoint inhibitors. (October 2021) - Nice, Laura; Bycroft, Ryan; Wu, Xiaoyong; Rai, Shesh N; Figg, Lindsay; Bhandari, Shruti; Burd, Megan
Introduction: Immune checkpoint inhibitors (ICIs) have become the standard of care in many cancer types. As the number of patients receiving ICIs for various cancers continues to expand, patients and practitioners should be aware of potentially severe immune-related adverse events (irAEs). Despite reports of the incidence of grade 3/4 toxicities, the proportion of patients whose symptoms were clinically severe enough to warrant hospitalization for adverse event management is unknown. Methods: This single center, retrospective, observational study was designed to determine the impact of irAEs on patients and the hospital. Patients who started ICIs from May 2016 through May 2019 for melanoma or lung cancer were included. The primary outcome was incidence of hospitalization for irAE. Secondary outcomes included median length of hospitalization, time to onset of irAE, rates of hospitalization for irAE per each checkpoint inhibitor regimen, organ system affected, progression free survival, and overall survival. Results: Of 384 patients with melanoma or lung cancer, 27 (7%) were hospitalized at our institution for an irAE. The most common irAE leading to hospitalization was colitis for patients with melanoma and pneumonitis for patients with lung cancer. The median length of stay across all hospitalizations was 10 days. Twenty-five patients required the use of corticosteroids while hospitalized, while eight of these patients required second line irAE treatment. For the total patient population, 34.7% experienced a grade 1/2 irAE and 13.1% experienced a grade 3/4 irAE. Conclusion: Our cohort of patients experienced similar rates irAEs as reported in clinical trials and published reports.